MODERN DIMENSION OF TASKS OF THE SCIENTIFIC ORGANIZATION OF THE EDUCATIONAL PROCESS OF TRAINING OF TEACHERS OF FINE ARTS IN THE SYSTEM OF ARTISTIC AND ARTISTIC - M.I. Reznichenko (Academy of Cognitive and Natural Sciences, 2022)
The urgent problems of scientific organization of educational process of préparation of the teachers of fine arts in system of art-pedagogical éducation on Ukraine are considered and the experience of job in this direction of art graphic faculty о/ the South-Ukrainian pedagogical university.